2021
DOI: 10.1109/ojcoms.2021.3131552
|View full text |Cite
|
Sign up to set email alerts
|

Secure and Efficient AKA Scheme and Uniform Handover Protocol for 5G Network Using Blockchain

Abstract: The fifth generation (5G) cellular network provides users with high-quality services due to its high transmission rate and low latency. It will support Internet of Things (IoT) devices and enable new applications in health, banking, education, etc. Security is essential in this network because vulnerabilities may be exploited to disrupt these applications which may directly impact our life. Authentication and key agreement (AKA) and handover (HO) are usually the target of cyberattacks in any cellular network. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…However, there is no formally proved protocol presented in the proposal. Haddad et al proposed a blockchain-based 5G authentication protocol based on a public blockchain in [10,11]. They suggested that all 5G access points (APs) can use the UE public keys listed in the blockchain to perform mutual authentication between the AP and the UE.…”
Section: Blockchain In 5g Authenticationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no formally proved protocol presented in the proposal. Haddad et al proposed a blockchain-based 5G authentication protocol based on a public blockchain in [10,11]. They suggested that all 5G access points (APs) can use the UE public keys listed in the blockchain to perform mutual authentication between the AP and the UE.…”
Section: Blockchain In 5g Authenticationmentioning
confidence: 99%
“…Overall, Table 1 summarizes all recent blockchain-based 5G authentication schemes and their challenges. Decentralized authentications with low overhead [9] No single trust authority [10,11] Decentralized authentication to nearby gNBs [12] Removal of obsolete data in blockchains [13] Inter-domain authentication [14] Improving 5G EAP-AKA protocol security [19] Formally verified protocol using chameleon signature [15] 5G Handover Authentication Efficient handover authentication [16] Optimized for frequent handover [17] Lightweight handover authentication [18] Traceability for base stations to record malicious devices FV = formally verified protocol; DA = device anonymity; PFS = perfect forward secrecy; LA = lightweight authentication; DoS = DoS attack prevention; DDoS = DDoS attack prevention.…”
Section: Blockchain In 5g Authenticationmentioning
confidence: 99%
“…๐ท๐‘€ ๐‘–๐‘— (๐›พ) = (๐ป๐‘‚ ๐‘–๐‘—๐›พ ) ๐ป๐‘‚ ๐‘–๐‘— (10) From the above Eqns. ( 9) and ( 10), '๐ป๐‘‚ ๐‘–๐‘— ' represents the number of handovers from mobile node '๐‘–' to mobile node '๐‘—', and '๐ป ๐‘› ' represents the total number of mobile node handovers.…”
Section: Figure 2 Block Diagram Of Markov Renewal Predictionbased Sea...mentioning
confidence: 99%
“…The CNN here allocated the resource in an efficient manner while the load balancing and error rate were handled using LSTM, therefore ensuring overall accuracy. Yet another uniform handover protocol using blockchain was designed by Haddad et al [10] with the objective of reducing computation overhead.…”
Section: Introductionmentioning
confidence: 99%